Fragments of oral History based on the Materials of Filtration and Investigation - ZhanbossinovаAlbina S.; Atantayeva, Bakyt Zh.; Mendyganym D. Shaimerdenova, Arman A. Kulshanova,; Zhirindinova, Kuralay R. (Opción, 2019)
The article reveals the issues of the history of the Turkestan Legion on the basis of regional archival materials introduced into scientific circulation for the first time via statistical, special historical and scientific methods at the intersection of interdisciplinary approaches. As a result, the inaccessibility of all archival materials does not yet allow to reveal all aspects of the activities of the participants of the Turkestan Legion. In conclusion, the content of the SMERSH protocols demonstrates the absence of ideological motifs among those who entered the Turkestan Legion, the urge to live was the impetus.